Accountants' involvement in corporate environmental governance in Malaysia: case evidence within the automotive industry / Noor Sufiawati Khairani - Khairani, Noor Sufiawati (UiTM Cawangan Johor, 2018)
This study investigates the involvement of corporate accountants in corporate environmental governance (CEG) of car manufacturers and assemblers within the Malaysian automotive industry. On the basis of System Thinking, proponents of CEG suggest that a firm and its subsystem which includes the people such as the corporate accountants should act as a system to successfully address the environmental issues. However, to date, only few studies have investigated on corporate accountants' involvement in CEG particularly within the Malaysian automotive industry context. This paper thus contributes to fill this gap in the literature by examining corporate accountants' involvement in CEG within the automotive industry in Malaysia. Adopting a single case study method, this exploratory study collects data through semi-structured interviews and document reviews from an automotive case firm operating in Malaysia. Consistent with the literature, the findings indicate limited active involvement of corporate accountants in the case firm's CEG. Nevertheless, a broad-based study involving manufacturing companies across industries in Malaysia may provide a better picture of the involvement of corporate accountants in CEG within the local scenario.